Innovative Oat‐Based Postbiotic and Synbiotic Products: Chemical Constituents and Hepatoprotective Efficacy - Ruixue Wen; Lanqi Zhou; Wei Song; Jiayao Lv; Tianqi Liu; Haizhou Wu; Lin Shi (eFood)
ABSTRACT Oat (Avena sativa) is a health‐promoting food exhibiting prebiotic properties. We invented oat‐based postbiotics (Oat_PB) fermented with probiotics (mainly Lactobacillus and Bifidobacterium) and comprehensively compared their chemical constitutions with the synbiotic form (Oat_SB). Oat_PB accumulated β‐glucan, avenanthramides (2c, 2p, and 2f) as well as free amino acids, for example, threonine, valine, arginine, aspartate, citrulline, and taurine, while reducing total phenol, flavone, and protein. Oat_PB enriched metabolites affecting lipid and glucose metabolism. Probiotics‐derived oat foods mitigated high‐sucrose‐induced obesity, liver injury, and repaired lipid and glucose metabolism in rats, with Oat_PB showing most pronounced effects. Oat_PB reversed high‐sucrose disturbed hepatic fatty acid profiles, and regulated genes and proteins involved in lipid homeostasis. Oat_PB ameliorated gut dysbacteriosis by increasing Alloprevotella, Prevotella, and Akkermansia while inhibiting harmful bacteria. Collectively, our study demonstrates the additional value of probiotic‐derived oat foods beyond the raw oat materials in preventing metabolic homeostasis and gut dysbacteriosis.